2013
DOI: 10.1161/circulationaha.113.003885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoperative Moderate/Severe Mitral Regurgitation on 2-Year Outcome After Transcatheter and Surgical Aortic Valve Replacement

Abstract: Background— The effect of preoperative mitral regurgitation (MR) on clinical outcomes of patients undergoing transcatheter aortic valve replacement (TAVR) is controversial. This study sought to examine the impact of moderate and severe MR on outcomes after TAVR and surgical aortic valve replacement (SAVR). Methods and Results— Data were drawn from the randomized Placement of Aortic Transcatheter Valve (PARTNER) Trial cohort A patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
108
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 26 publications
6
108
1
6
Order By: Relevance
“…An analysis from the PARTNER trial similarly showed that significant MR was associated with an HR of 1.77 for 2‐year mortality post‐SAVR 32. Despite the impact of MR on mortality, the optimal management of such patients with moderate MR undergoing SAVR is not clear, given that the operative risk of double‐valve surgery continues to be markedly greater than single‐valve surgery 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…An analysis from the PARTNER trial similarly showed that significant MR was associated with an HR of 1.77 for 2‐year mortality post‐SAVR 32. Despite the impact of MR on mortality, the optimal management of such patients with moderate MR undergoing SAVR is not clear, given that the operative risk of double‐valve surgery continues to be markedly greater than single‐valve surgery 33, 34…”
Section: Discussionmentioning
confidence: 99%
“…Takeda et al 9 showed a significantly higher rate of re-hospitalization for heart failure in patients with concomitant significant MR compared with non/trivial and, among patients with significant Mr, a trend for a higher re-admission rate for patients without any improvement in Mr after aVr. on the other hand, the partNer study 7 showed an improvement in Nyha functional class after both surgical aVr and taVr which was independent on the presence and severity of concomitant Mr. a similar result emerged from a study by toggweiler et al 12 on patients undergoing taVr, with a general improvement in Nyha class regardless of Mr grade.…”
Section: Significant Mr and Functional Status In Patients Undergoing Avrmentioning
confidence: 59%
“…a 2011 meta-analysis performed on 17 studies concluded that patients with moderate/severe Mr had higher mortality compared to mild or no Mr at 30 days (or 0.41; CI at 95%: 0.24-0.72), and worse survival at 3 years (hr 0.49; CI at 95%: 0.35-0.69), 5 years (hr 0.46; CI at 95%: 0.34-0.61) and 10 years (hr 0.61; CI at 95%: 0.40-0.92)after aVr 10 . More recently, the partNer study 7 showed an increased mortality during a 24 months follow-up in patients with significant MR among 299 patients undergoing surgical aVr (hr 1.96; CI at 95%: 1.26-3.06).…”
Section: Impact Of Significant Mr On Mortality In Patients Undergoingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with SAS and mitral regurgitation included in the PART-NER trial had a higher mortality rate at follow-up with isolated SAVR in comparison with TAVR without mitral valve repair or replacement [28].…”
mentioning
confidence: 99%